Kucecwara Chic, Ragam Fungsi Untuk Malang Dalam Batikku Siswiyani - Syarafina, Nanda; Nurhadi, Nurhadi; Riska, Yuliana; Cynthia, Persijn Ayura; Dyah, Ratnasari Siwi (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
Batik Unfortunate yet widely known both nationally and internationally. Batik Malangan able to penetrate world markets, in particular the intended market share are the young people and the general public. The idea was to create a bag that can be personalised way it functions with a touch of Malangan batik motifs with the name "Kucecwara Chic". The methods used in marketing this product is by using a feasibility study of this aspect of the market, technical aspects, aspects of management, financial aspects and environmental aspects. Later these aspects will be the guidelines to continue this effort to more worthy and more profit. Expected by creating products with the name Kucecwara Chic, this product can be used for fashion and religious but also keep bringing the unfortunate culture, the usefulness of this Chic is Kucecwara products enhance the value to the product so that it becomes a multifunctional product can be converted into a bag, holster, belt, mini, prayer mats and scarves, headdresses as a media preservation and introduction to batik malang in the national and international scene and can deceive the human resource community are concerned. Keywords : Kucecwara Chic, Batik